Increased Haematopoietic Supportive Function of USSC from Umbilical Cord Blood Compared to CB MSC and Possible Role of DLK-1 - Simone Maria Kluth; Teja Falk Radke; Gesine Kögler (Hindawi Limited, 2013)
Multipotent stromal cells can be isolated from a variety of different tissues in the body. In contrast to stromal cells from the adult bone marrow (BM) or adipose tissue, cord blood (CB) multipotent stromal cells (MSC) are biologically younger. Since first being described by our group, delta like 1 homologue (DLK-1) was determined as a discriminating factor between the distinct cord blood-derived subpopulations: the unrestricted somatic stromal cells (USSC), which lack adipogenic differentiation capacity, and the BM MSC-like CB MSC. In this study, experiments assessing the haematopoiesis-supporting capacity and molecular biological analyses were conducted and clearly confirmed different properties. Compared to CB MSC, USSC lead to a higher expansion of haematopoietic cells and in addition express significantly higher levels of insulin-like growth factor binding protein 1 (IGFBP1), but lower levels of IGF2. The data presented here also indicate that DLK-1 might not be the sole factor responsible for the inhibition of adipogenic differentiation potential in USSC but nevertheless indicates a biological diversity among cord blood-derived stromal cells.